Follicular lymphoma associated paraneoplastic myositis. Issue 10 (23rd July 2020) - Melody, Megan; Parrondo, Ricardo; Alhaj Moustafa, Muhamad; Wu, Kevin; Menke, David; Seim, Lynsey; Tun, Han W.
Abstract: This case illustrates an unusual presentation of paraneoplastic myositis in stage IV follicular lymphoma managed with high‐dose steroids, a previously unreported entity in the literature. Abstract : This case illustrates an unusual presentation of paraneoplastic myositis in stage IV follicular lymphoma managed with high‐dose steroids, a previously unreported entity in the literature.